Bureaucratic Corruption and Human Development in Sub-Saharan Africa: A Comparative Case-Study of Cameroon and Botswana - Fon, Nguh Nwei Asanga (Sage Publications Inc, 2025)
This paper probes into the impact of corruption on development by looking at the correlation between bureaucratic corruption and human development in two Sub-Saharan African countries: Cameroon and Botswana. Methodologically, it is a comparative case-study analysis based on the principal-agent theory and the principal-agent-client (PAC) model. Using empirical evidence in both quantitative and qualitative data from both countries this paper compares their performances on bureaucratic corruption and assesses the impact of these performances on human development. The factual evidences uncovered from both countries show a positive correlation between high anti-corruption performance and high human development and vice versa.
Keywords: Bureaucratic corruption; human development; Sub-Saharan Africa; Cameroon; Botswana